Response of Parasite Community Composition to Aquatic Pollution in Common Carp (Cyprinus carpio L.): A Semi-Experimental Study - Pravdová, Markéta; Kolářová, Jitka; Grabicová, Kateřina; Janáč, Michal; Randák, Tomáš; Ondračková, Markéta (Animals, 2023)
The response of parasite communities to aquatic contamination has been shown to vary with both type of pollutant and parasite lifestyle. In this semi-experimental study, we examined uptake of pharmaceutical compounds in common carp (Cyprinus carpio L.) restocked from a control pond to a treatment pond fed with organic pollution from a sewage treatment plant and assessed changes in parasite community composition and fish biometric parameters. The parasite community of restocked fish changed over the six-month exposure period, and the composition of pharmaceutical compounds in the liver and brain was almost the same as that in fish living in the treatment pond their whole life. While fish size and weight were significantly higher in both treatment groups compared to the control, condition indices, including condition factor, hepatosomatic index, and splenosomatic index, were significantly higher in control fish. Parasite diversity and species richness decreased at the polluted site, alongside a significant increase in the abundance of a single parasite species, Gyrodactylus sprostonae. Oviparous monogeneans of the Dactylogyridae and Diplozoidae families and parasitic crustaceans responded to pollution with a significant decrease in abundance, the reduction in numbers most likely related to the sensitivity of their free-living stages to pollution.
Keywords: condition; sewage treatment plant; environmental load; pharmaceuticals; ectoparasites; endoparasites; fish parasites